Mediator analysis of job embeddedness: Relationship between work-life balance practices and turnover intentions. Issue 5 (7th August 2017) - Thakur, Shweta Jaiswal; Bhatnagar, Jyotsna
Abstract : Purpose: The purpose of this paper is to investigate the mediating effect of job embeddedness on the relationship between work-life balance practices (WLBP), which include accessibility (AWLBP), current utilisation (CWLBP) and perceived future use (FWLBP) of these practices, as well as employees' intentions to stay (ITS). This research is based on conservation of resources theory. Design/methodology/approach: This study uses a survey method and a structured questionnaire to collect data from people working in diverse industries. A regression analysis is used to measure the direct effects of the hypothesised relationships. The Sobel test and Baron and Kenny mediation analysis were used to measure the indirect effects of the hypothesised relationship. Findings: AWLBP, CWLBP and FWLBP are found to foster job embeddedness and turnover intention. Job embeddedness fully mediates the relationship between AWLBP, CWLBP, FWLBP and ITS. Practical implications: Human resources (HR) managers should introduce WLBP to create a web of contextual and perceptual forces that embed employees in the organisation and encourage them to stay. Factors that affect employee attraction and retention change with time, career and life stage; therefore, it is important to assess the future needs of employees to augment retention. HR managers should proactively attempt to enhance embeddedness by offering customised WLBP and by dealing with the signs of low embeddedness before it results in voluntary turnover. Originality/value: This study attempts to integrate two streams of research (job embeddedness and WLBP), which, despite being similar in focus, have developed independently of each other. This is one of the first studies to incorporate access to, utilisation and perceived future use of these practices in a single study. It also adds to the literature by investigating antecedents of job embeddedness and analysing it as a mediator between WLBP and ITS, which has been highlighted as a gap in the literature.